2008
DOI: 10.1007/s10529-008-9784-4
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of DNA with protein using His-tag chemistry and its application to the aptamer-based detection system

Abstract: We propose a novel method to prepare a DNA-protein conjugate using histidine-tag (His-tag) chemistry. Oligo-DNA was modified with nitrilotriacetate (NTA), which has high affinity to a His-tag on recombinant protein via the complexation of Ni(2+). Investigations using a microplate which displayed a complementary DNA-strand revealed that a NTA-modified DNA-protein conjugate was formed and immobilized in the presence of Ni(2+) on the microplate. We then adopted alkaline phosphatase (AP) as a model protein, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 20 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…25 ODFs chemically resemble DNA, and thus one might make use of methodologies of protein conjugation that have been developed for DNA itself; 26-29 however, to our knowledge, DNA has yet to be conjugated to proteins via the haloalkane dehalogenase approach. Here we have developed a general strategy for genetically-encoded labeling of proteins with ODF fluorophores (and potentially with DNA as well), by employing the HaloTag haloalkane dehalogenase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…25 ODFs chemically resemble DNA, and thus one might make use of methodologies of protein conjugation that have been developed for DNA itself; 26-29 however, to our knowledge, DNA has yet to be conjugated to proteins via the haloalkane dehalogenase approach. Here we have developed a general strategy for genetically-encoded labeling of proteins with ODF fluorophores (and potentially with DNA as well), by employing the HaloTag haloalkane dehalogenase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Ni 2+ -NTA has been used to immobilize His 6 -tagged proteins on agarose beads [2], microtiter plates [4], and lipid surfaces [5 - 9]. It has also been exploited in protein-labeling schemes where Ni 2+ -NTA has been coupled to horseradish peroxidase [10], oligonucleotides [11; 12], biotin [13], and nano-gold particles [14; 15]. This plethora of applications of the Ni 2+ -NTA/His 6 -tag technology is a testament to the value and flexibility of this metal chelation system.…”
Section: Introductionmentioning
confidence: 99%
“…On the other end of the tether, the protein of interest is either covalently linked through a thiol-maleimide crosslink (23) or tethered non-covalently via the histidine tag to Anti-his antibodies, which in turn are covalently linked to aminated DNA tethers (29). The histidine tag of proteins was used previously to non-covalently link to DNA (35–38) and directly attaching proteins to NTA-modified AFM tips (39). It was demonstrated that the His-Ni-NTA bond is stable enough (~120pN at 400pN/s) to facilitate single-molecule force spectroscopy (SMFS) experiments of the tethered protein (40–43) thus allowing AFM-based studies measuring unbinding forces of CBM3a using Ni-NTA (25),(27).…”
Section: Introductionmentioning
confidence: 99%